2021
DOI: 10.1111/cea.14016
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative and quantitative comparison of IgE antibody profiles with two multiplex platforms for component‐resolved diagnostics in allergic patients

Abstract: Background Clinically complex phenotypes require more and more sophisticated and comprehensive diagnostic approaches, able to discriminate genuine sensitizations from cross‐reactivity. Interpretative complexity of multiplex diagnostic arrays has somewhat limited their diffusion. This study compares two currently available methods, namely ISAC® test and ALEX2® test. Methods In total, 140 allergic individuals, with a history of atopic dermatitis, adverse food reactions, allergic rhinitis and/or bronchial asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
4
18
1
2
Order By: Relevance
“…In a subset randomly selected (98 individuals, 48 from North Italy and 50 from Center-South Italy) a more in-depth evaluation was carried out by the Allergy Explorer-ALEX2Ò (Macroarray Diagnostics, Vienna) multiplex platform evaluating a broader profile of shellfish molecules, 13 including Pen m 1 (tropomyosin), Pen m 2 (arginine kinase), Pen m 3 (myosin light chain), and Pen m 4 (sarcoplasmic calcium-binding protein) all from Black-Tiger shrimp (Penaeus monodon), Cra c 6 (the troponin-c from brown shrimp, Crangon crangon), Der p 10 (tropomyosin), and Der p 11 (paramyosin) both from Dermatophagoides pteronyssinus, as well as of shellfish extract including crab, lobster, northern shrimp, white shrimp, squid, mussel, oyster, clam, and scallop. IgE levels >0.3kUA/L were considered positive as per the manufacturer's instructions.…”
Section: Data Sources/measurementmentioning
confidence: 99%
“…In a subset randomly selected (98 individuals, 48 from North Italy and 50 from Center-South Italy) a more in-depth evaluation was carried out by the Allergy Explorer-ALEX2Ò (Macroarray Diagnostics, Vienna) multiplex platform evaluating a broader profile of shellfish molecules, 13 including Pen m 1 (tropomyosin), Pen m 2 (arginine kinase), Pen m 3 (myosin light chain), and Pen m 4 (sarcoplasmic calcium-binding protein) all from Black-Tiger shrimp (Penaeus monodon), Cra c 6 (the troponin-c from brown shrimp, Crangon crangon), Der p 10 (tropomyosin), and Der p 11 (paramyosin) both from Dermatophagoides pteronyssinus, as well as of shellfish extract including crab, lobster, northern shrimp, white shrimp, squid, mussel, oyster, clam, and scallop. IgE levels >0.3kUA/L were considered positive as per the manufacturer's instructions.…”
Section: Data Sources/measurementmentioning
confidence: 99%
“…This has made it possible to investigate novel molecular recognition profiles. 91 By comparing one another the structural identity of these molecules, it is possible to observe how these form clusters that largely depend on their botanical origins and phylogenetic relationships. For instance, the 2 nsLTPs of 7 kD form a cluster, as do grape (Vitis vinifera) nsLTP, Vit v 1, and hemp (Cannabis sativa) nsLTP, Can s 3, or apple (Malus domestica) Mal d 3 and Pru p3 (Figure 2).…”
Section: The Relevance Of Pollen Ltps and The Question Of The Primary...mentioning
confidence: 99%
“…Recently, additional nsLTP molecules, showing a molecular weight of either 7 kDa or 9 kDa, have become available for in vitro diagnostics by multiplex tests. This has made it possible to investigate novel molecular recognition profiles 91 …”
Section: Introductionmentioning
confidence: 99%
“…ALEX and ISAC share 102 common inhalation-and food-derived allergen components. Previous studies [1][2][3][4] showed good agreement between ALEX and ISAC, however none of these studies related both their sensitization results directly to clinical relevant allergies, neither discussed the impact on clinical decision making in children with food allergy.…”
mentioning
confidence: 99%
“…Both ALEX and ISAC are solid-phase immunoassays which enable the detection of sIgE to multiple individual allergen components. When comparing these multiplex arrays one should be aware that both platforms employ different methodologies and units of measurement [5], and in addition ALEX uses a CCD inhibitor while ISAC does not [1][2][3]5]. ALEX reports its results as kUA/L, similar as Immu-noCAP, classified in five different categories (Fig.…”
mentioning
confidence: 99%